Chapter 12. Phonology: From Old Rusian to Modern Russian - Nesset, Tore (Septentrio Educational, 2015)
Why does Modern Russian have mobile vowels, such as /o/ in сон ‘dream’, which disappear in inflected forms such as the genitive singular сна? Why can the letters к, г, х be followed by и, but not ы? Why is род ‘family’ pronounced with [t] at the end, when it is spelled with the letter д, and why is легко ‘easy’ spelled with the letter г? This chapter shows that this and many other problems you have struggled with in Modern Russian are the result of phonological changes in medieval times. Download the video to learn more.